2020
DOI: 10.21098/jimf.v6i2.1091
|View full text |Cite
|
Sign up to set email alerts
|

Islamic vs Conventional Funds Within the Family: Selectivity Skills and Market Timing Ability

Abstract: ABSTRACT The aim of the study is to compare the performance of Islamic mutual fund (IMF) and conventional mutual fund (CMF) within the same family, in addition, to examine the performance of fund family in Malaysia for the period from 2007 to 2018. The study used eight measures of performance, raw returns, excess returns, Sharpe ratio, Treynor ratio, Jensen alpha, Carhart four-factor model as selectivity models, In addition to Treynor & Mazuy (TM) and Hendrickson & Merton (HM) as market timing mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…However, the results of this study support the findings of Božović (2021), who identified a significant role for mutual fund managers but also acknowledged the presence of luck as a contributing factor in mutual fund performance. Additionally, this study's findings align with those of Atta and Marzuki (2020) Net-Selectivity -0.0789 -0.0613 -0.059 -0.0719 -0.0996 -0.0933 -0.1104 -0.1320 -0.1261 -0.1253 -0.1150…”
Section: Treynor-mazuy and Fama Net-selectivity Modelsupporting
confidence: 84%
See 2 more Smart Citations
“…However, the results of this study support the findings of Božović (2021), who identified a significant role for mutual fund managers but also acknowledged the presence of luck as a contributing factor in mutual fund performance. Additionally, this study's findings align with those of Atta and Marzuki (2020) Net-Selectivity -0.0789 -0.0613 -0.059 -0.0719 -0.0996 -0.0933 -0.1104 -0.1320 -0.1261 -0.1253 -0.1150…”
Section: Treynor-mazuy and Fama Net-selectivity Modelsupporting
confidence: 84%
“…They are responsible for setting the fund's investment strategy, selecting the securities within the portfolio, and managing the fund's assets continuingly. The manager's skill is particularly relevant for actively managed funds where investment decisions are made based on the manager's discretion rather than passively tracking an index (Atta & Marzuki, 2020). The performance of a mutual fund is often evaluated by comparing its returns to a benchmark index or similar funds in the same category.…”
Section: Mutual Fund Performance and Managers' Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of researchers have argued that the performance of companies is not determined only by one factor or two factors; there is a multiple set of variables that affect the level of financial performance, and these variables may be non-financial or financial, such as the size of the company, the ratio of debt, liquidity, and operating profit. Some of the studies that have been referred to previously discussed the impact of additional v ariables that control the level of financial performance in addition to intangible assets (Atta & Marzuki, 2020). The study by Gamayuni (2015) tested the impact of debt size on the association between the intangibility of assets and financial adequacy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, their analysis confirmed both Islamic and conventional funds' asymmetric and convex flow-performance relationships, as well as investors' best-performance-chasing behaviour. SRI funds have shown an asymmetric relationship between flow and performance; that is, investors' reaction to negative outcomes is not as aggressive as it is to positive returns (Azmi et al, 2018 Marzuki (2020) found that the characteristics of fund families affected both Islamic and conventional funds within the family.…”
Section: Previous Studiesmentioning
confidence: 99%